An evaluation of resurgence following functional communication training conducted in alternative antecedent contexts via telehealth. Issue 1 (16th October 2019) - Suess, Alyssa N.; Schieltz, Kelly M.; Wacker, David P.; Detrick, Jessica; Podlesnik, Christopher A.
Abstract : Treatments based on differential reinforcement may inadvertently increase the recurrence of problem behavior in the face of challenges because reinforcers for appropriate behavior occur in the same context as problem behavior. The current study evaluated one potential approach to mitigating these problems with differential reinforcement treatments based on behavioral momentum theory. Specifically, appropriate behavior was trained in contexts without a history of reinforcement prior to intervening with problem behavior. Participants were 4 children with autism spectrum disorder. Treatment used telehealth to implement functional communication training (FCT) in three alternative contexts with minimal or no history of reinforcement for problem behavior before initiating FCT in the treatment context. Evaluations of the effects of treatment and tests of resurgence were conducted intermittently during treatment to evaluate maintenance. When FCT treatment was initiated in alternative contexts, initial results were comparable to more typical implementations of FCT. Resurgence was reduced to similar levels during tests of resurgence for all participants when compared to more typical previously published implementations of FCT, but clinically significant reductions in resurgence occurred more quickly in the present study. These findings support training appropriate behavior in an alternative context to mitigate the resurgence of problem behavior during differential reinforcement treatments.